Is fiscal decentralization growth enhancing? A cross-country study in developing countries over the period 1990-2014 - Kumba Digdowiseiso (Economies, 2022)
For several decades, many scholars have widely debated the nexus between devolution of fiscal powers and efficiency. However, several studies have neglected the role of institutions and other institutional settings in fiscal decentralization. This study augments the literature by revisiting the fiscal decentralization-growth nexus regarding institutional quality in 24 developing countries over the period 1990-2014. By using estimators of fixed effects (FE), random effects (RE), and the system generalized method of moments (GMM), it is shown that growth depends on the level of fiscal authority and its interaction with institutions. In this case, increasing the extent of cosharing has a detrimental effect on growth in countries with poor governance, a high risk of corruption, and nondemocratic governments. However, shared rule contributes to growth by enhancing the degree of law and order and the quality of bureaucracy.
Keywords: 330; developing countries; economic growth; fiscal decentralization; institutional quality